ANSWER: I can give you the steps to figure out this question.
1 if it is starting at the 6 on the y axis, then just do up 1 over 1 until you get to the 10
The answer to your question is..... 6y+1=4x+10
Answer:
no solution
Step-by-step explanation:
Given the 2 equations
y =
x + 4 → (1)
-
x + y = - 5 → (2)
Substitute y =
x + 4 into (2)
-
x +
x + 4 = - 5 , that is
4 = - 5 ← not possible
This indicates the system has no solution
0.8 = 8/10
simplified = 4/5 seconds
hope this helps
Answer: ![x=\frac{12}{7}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B12%7D%7B7%7D)
Step-by-step explanation:
Remember the logarithms properties:
![log(m)-log(n)=log(\frac{m}{n})\\\\b^{log_b(a)}=a](https://tex.z-dn.net/?f=log%28m%29-log%28n%29%3Dlog%28%5Cfrac%7Bm%7D%7Bn%7D%29%5C%5C%5C%5Cb%5E%7Blog_b%28a%29%7D%3Da)
Then,simplifying:
![log_{8}(\frac{x}{-2x+4}) = log_{8}(3)](https://tex.z-dn.net/?f=log_%7B8%7D%28%5Cfrac%7Bx%7D%7B-2x%2B4%7D%29%20%3D%20log_%7B8%7D%283%29)
Apply base 8 to boths sides and then solve for "x":
![8^{log_{8}(\frac{x}{-2x+4})}=8^{log_{8}(3)}\\\\\frac{x}{-2x+4}=3\\\\x=3(-2x+4)\\\\x=-6x+12\\x+6x=12\\7x=12\\\\x=\frac{12}{7}](https://tex.z-dn.net/?f=8%5E%7Blog_%7B8%7D%28%5Cfrac%7Bx%7D%7B-2x%2B4%7D%29%7D%3D8%5E%7Blog_%7B8%7D%283%29%7D%5C%5C%5C%5C%5Cfrac%7Bx%7D%7B-2x%2B4%7D%3D3%5C%5C%5C%5Cx%3D3%28-2x%2B4%29%5C%5C%5C%5Cx%3D-6x%2B12%5C%5Cx%2B6x%3D12%5C%5C7x%3D12%5C%5C%5C%5Cx%3D%5Cfrac%7B12%7D%7B7%7D)
8 is the answer cuz if you dive and all that